FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK ATAS PENGGELAPAN PAJAK - Vinna Marthadilova; Vince Ratnawati; Andreas Andreas (PEKBIS, 2018)
This study aims to analyze the factors influencing the perception of taxpayers on tax evasion with taxation sanctions as a moderating variable. The endogenous variables in this study are the perception of taxpayers on tax evasion and tax morals, while the exogenous variables are tax fairness, tax knowledge, enforcement level, social exchange, and tax sanctions as moderating variable. The population of this study are corporate taxpayer in Pekanbaru. While the sample of this study is a corporate taxpayer registered in Directorate General of Taxes in Pekanbaru are 150 respondents. Data analysis of this study uses Structural Equation Model with warp PLS 5.0. The results showed that tax moral mediates the relationship between fairness to the perception of taxpayers on tax evasion as full mediation, and also tax moral mediates the relationship between the enforcement level to the perception of taxpayers on tax evasion as a partial mediation. However tax moral does not mediate the relationship between tax knowledge to the perception of taxpayers on tax evasion, and also tax moral does not mediate the relationship between social exchange to the perception of taxpayers on tax evasion. On the other hand, tax sanction moderates the relationship of tax moral to the perception of taxpayers on tax evasion